2018
DOI: 10.1021/jacs.8b05156
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of a Nontrigonal Phosphorus Ligand into a Transition Metal-Hydride: Direct Access to a Metallohydrophosphorane

Abstract: The synthesis and reactivity of an NPN-chelating ligand containing a nontrigonal phosphorous triamide center (L1 = P(N(o-N(2-pyridyl)C6H4)2) is reported. Metalation of L1 with RuCl2(PPh3)3 gives RuCl2(PPh3)(L1) (2). By contrast, metalation of L1 with RuHCl(CO)(PPh3)3 yields RuCl(CO)(PPh3)(L1H) (3), a chelated 10-P-5 ruthenahydridophosphorane, via net insertion into the Ru–H bond. Hydride abstraction from 3 with Ph3CPF6 gives [RuCl(CO)(PPh3)(L1)]PF6 (4); reaction of 4 with NaBH4 returns 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…The arising biphilicity is shown upon complexation of the hydride complex [RuHCl(CO)(PPh 3 ) 3 ]. 69 Instead of coordination of the phosphorus ligand, the insertion product 8 was obtained (Scheme 5). Based on NMR measurements and DFT calculations, the reaction product is best described as an unprecedented metallohydrophosphorane complex.…”
Section: Implication For Transition Metal Chemistrymentioning
confidence: 99%
“…The arising biphilicity is shown upon complexation of the hydride complex [RuHCl(CO)(PPh 3 ) 3 ]. 69 Instead of coordination of the phosphorus ligand, the insertion product 8 was obtained (Scheme 5). Based on NMR measurements and DFT calculations, the reaction product is best described as an unprecedented metallohydrophosphorane complex.…”
Section: Implication For Transition Metal Chemistrymentioning
confidence: 99%
“…[9][10][11][12] Motivated by the perception that the restriction of phosphorus to local (pseudo)trigonal symmetry places an unnecessary check on the synthetic performance of s 3 -P compounds, [13][14][15][16][17][18][19][20][21][22][23] we have advanced the hypothesis that descent from trigonal symmetry should colocalize both donor and acceptor reactivity at as ingle s 3 -P site (i.e., biphilic [24] reactivity). Indeed, we have shown that nontrigonal s 3 -P compounds (see 1 and 2,F igure 1a)e volve to pentacoordinate phosphorus (s 5 -P) products through oxidative addition of EÀHb onds (E = OR, NHR, Ru), [25][26][27][28] in some cases reversibly. [29][30][31][32][33][34][35] Although applications of the biphilic character of nontrigonal s 3 -P compounds such as 1 and 2 have emerged in reactivity,adirect experimental demonstration of how the C 3v !C s structural deformation controls s 3 -P frontier orbital energies has not been previously presented.…”
mentioning
confidence: 99%
“…When redissolved in benzene, a 31 P NMR spectrum of the precipitate shows a single peak whose chemical shift (δ -19 ppm) suggests a pentacoordinate phosphorus environment. [28,34,35] By 1 H NMR spectroscopy, both the Nmethyl groups of the triamide ligand as well as the tert-butyl groups of the nitroso fragment are found to be inequivalent. Both the 31 P and 13 C NMR spectrum provide evidence for coupling between phosphorus and an ortho carbon atom of the nitrosoarene fragment with a magnitude ( 1 JC-P = 154 Hz)…”
Section: Resultsmentioning
confidence: 99%